A Case Study of Migration to an Open Source ILS: Partnership among State Libraries - Singh, Vandana (Qualitative and Quantitative Methods in Libraries; 2014: Special Issue: Social Justice, Social Inclusion, 2017)
This case study will describe the experiences of librarians in a small consortium and their collaboration with the state library during the process of migration to an open source integrated library system (ILS). Social justice is conceptualized in terms of policies, such as the “redistribution of goods and resources to improve the situation of the disadvantaged” (Bankston, 2010). With this understanding of social justice—issues of resources, power balance and negotiations—will be discussed using case study as a methodology. The objective of this case study is to understand the roles played by different stakeholders and the power dynamics of such a collaboration through the lens of social justice.